A value-oriented creative approach to a future science teacher training at the present stage - Aksinya Egorovna Egorova; Marina Petrovna Andreeva (Вестник Майкопского государственного технологического университета, 2023)
Relevance. Preparing students for teaching is a rather complex and difficult process, it is associated with many reasons, such as the unattractiveness (non-prestige) of a teacher’s profession for school graduates, the lack of competition for admission, the poor school preparation of first-year students, etc. These are just some of the reasons why it is quite difficult for many students to form and develop the motivation to master the profession in the real process.Formulation of the problem. How to make the university training of a future teacher the most effective? What conditions are necessary for the students to treat learning activities as preparation for their future profession?The purpose of the research is to determine the methodological ways and conditions for the formation of a value attitude towards one’s future profession.The research methods used are theoretical analysis of the best practices for preparing students for a profession, a comprehensive pedagogical experiment.The results. When students pass the technological scheme: Motivation – Theory – Modeling –Reflection – Theory – Training – Reflection – Correction – Activity – Reflection – the image “I am a future teacher”, there is an awareness of the importance of acquiring professional knowledge and skills, professional intentions are strengthened.Key findings. A creative value approach is one of the ways to form positive motivation, understanding the importance and value of professional knowledge, skills and competencies. At the same time, special conditions for active learning activities are created, a student sees the results of work himself, begins to be critical of his actions, paving the way for creativity and creative activity.